2021
DOI: 10.1186/s12889-021-11305-7
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of providers’ perceptions of parental feeding practices of infants and toddlers to prevent childhood obesity

Abstract: Background With a recent focus on establishing US Dietary Guidance for children ages 0 to 2 years old, the objective of this qualitative study was to determine misconceptions and barriers that prevent parents from implementing early childhood feeding and obesity prevention practices as reported by healthcare, community-based, and education providers. Methods Trained researchers conducted one-on-one qualitative phone interviews, using a semi-structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…It is vital that we identify ways to support parents who rely on NPC and the caregivers who provide care. A recent qualitative study with early childhood professionals revealed that ITS is a common area where parents need more support and reported needing more nutrition education materials for educating and engaging with parents on early feeding practices, including culturally representative information 43 . Findings from the current study underscore the need for the development and accessibility of resources for those caring for and feeding infants and young children.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…It is vital that we identify ways to support parents who rely on NPC and the caregivers who provide care. A recent qualitative study with early childhood professionals revealed that ITS is a common area where parents need more support and reported needing more nutrition education materials for educating and engaging with parents on early feeding practices, including culturally representative information 43 . Findings from the current study underscore the need for the development and accessibility of resources for those caring for and feeding infants and young children.…”
Section: Discussionmentioning
confidence: 72%
“…Less desirable infant feeding practices among nonparental caregivers have been linked to increased child weight, 30 however, providers may lack access to resources or information needed to enact more desirable infant feeding practices. 43 Third, NPC has been defined in a myriad of ways. A similar study categorized NPC groups as relative care, informal care, formal care, and combinations of those types of care; infants who were received more than one type of NPC or were in relative care demonstrated higher weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, parents expressed interest in using a child-feeding mobile phone app like BabyByte for accessing feeding-related guidance for children ages 0–2 years. With current parental confusion surrounding early childhood feeding [ 14 , 24 ] and reported nutrition education needs by parents [ 33 , 34 ] for early childhood obesity prevention, an app like BabyByte may be helpful as an intervention option. This is especially true for family members who may be more difficult to reach or less willing to commit to in-person meetings or sessions [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Age groups were organized based on optimal developmental feeding milestones. Content for the app prototype was based on early childhood obesity prevention information and related features based on priority topics identified by the target population from prior research conducted by the corresponding author [ 32 , 33 , 34 ] and key strategies from the Robert Wood Johnson Foundation’s (RWJF) Feeding Guidelines for Infants and Young Toddlers: A Responsive Parenting Approach [ 24 ]. These topics included when and how to introduce solid foods, how to safely introduce allergenic foods, how to encourage autonomy and self-regulation, and how to increase the variety and healthy food options in a young child’s diet.…”
Section: Methodsmentioning
confidence: 99%